Excerpts from Elias Khoury, Stella Maris, Trans. Yehouda Shenhav-Shaharabani (Rishon LeZion: Yedioth Books and Van Leer Institute Press, 2019) (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2020)
Excerpts from Elias Khoury, Stella Maris, Trans. Yehouda Shenhav-Shaharabani